Colonoscopic Findings in Patients with Chronic Diarrhea at Mohammad Hoesin Hospital Palembang - Imam Supriyanto; Suyata Suyata; Syadra Bardiman Rasyad; Fuad Bakry (The Indonesian Society for Digestive Endoscopy, 2013)
Background: Chronic diarrhea is a common problem encountered by clinicians. Colonoscopy is a tool with high accuracy and sensitivity to depict abnormalities and has the advantage in distinguishing the abnormalities that cause chronic diarrhea. Nevertheless, the colonoscopic findings in patients with chronic diarrhea vary by age. The objective of this study is to observe abnormalities found in lower gastrointestinal tract in patients withchronic diarrhea who underwent colonoscopy and its relationship with age.Method: An observational analytic study, data retrieved from medical record of outpatient and inpatient with chronic diarrhea at Mohammad Hoesin Hospital Palembang from January 2011 until December 2012. Chronic diarrhea diagnosis was based on clinical findings, laboratory result, and colonoscopy procedure. Patients were then divided into groups based on age ( 40 and 40). Data were analyzed with SPSS 12.0.Results: There were 92 patients consisted of 56 (60.9%) male and 36 (39.1%) female. Mean age was 47.67 ± 16.83 with age interval 15-85 years. Group I of 35 (38%) patients, whereas group II of 57 (62%) patients. The colonoscopic findings were ulcerative colitis 33 (35.9%), normal 27 (29.3%), colon tumor 20 (21.7%), colitis tuberculosis 5 (5.4%), Crohn’s disease 3 (3.3%) and polyp 4 (4.3%). Based on age, the incidence of ulcerative colitis was most frequently encountered in both groups, whereas normal colon and colon tumors were encountered most in group II. No correlation was found between age and colon abnormality (p = 0.87).Conclusion: The most common finding was ulcerative colitis followed by normal colon and colon tumor. There was no correlation between age and colon abnormalities.Keywords: chronic diarrhea, colonoscopy, age